The Effect of Traditional Games (Bentengan and Boy-Boyan) and Learning Interest on Elementary School Students’ Physical Fitness - Ardo Yulpiko Putra; Lolia Manurizal; Rian Diusmar (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2026)
The suboptimal physical fitness of elementary school students indicates the need for more engaging physical education strategies. Traditional games can serve as alternative learning activities that enhance both physical activity and students’ learning interest. This study aims to examine the effects of traditional games (Bentengan and Boy-boyan) and learning interest on students’ physical fitness, as well as their interaction. A 2×2 factorial experimental design was employed with 20 students selected using upper and lower 27% grouping. Physical fitness was measured using the Indonesian Physical Fitness Test (TKJI), while learning interest was assessed through a Likert-scale questionnaire. Data were analyzed using two-way ANOVA. The results show that both the type of traditional game (F = 15.207; p = 0.001) and learning interest (F = 7.759; p = 0.013) have significant effects on physical fitness, with a significant interaction effect (F = 18.241; p = 0.001). Bentengan proved more effective than Boy-boyan in improving students’ physical fitness.